2008
DOI: 10.1007/s00894-008-0270-7
|View full text |Cite
|
Sign up to set email alerts
|

Hologram and 3D-quantitative structure toxicity relationship studies of azo dyes

Abstract: Amino azobenzenes are important dyes in the food and textile industry but their application is limited due to their mutagenicity. Computational modeling techniques were used to help understand the factors responsible for mutagenicity, and several quantitative structure toxicity relationship (QSTR) models have been derived. HQSTR (hologram QSTR) analyses indicated that different substituents at sites on both rings contribute to mutagenicity. Fragment parameters such as bond (B) and connectivity(C), as well as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…For example, 2-methoxy-4-aminoazobenzene is an extremely weak mutagen, whereas 3-methoxy-4-aminoazobenzene is a strong hepatocarcinogen and mutagen (Esancy et al, 1990;Garg et al, 2002). Likewise, the presence of sulphonic groups on aromatic amines decreases their mutagenicity whereas the acetoxy Aromatic amines formed during anoxic conditions Dafale et al (2010) (COCH 3 ) substituent increases their mutagenic effects (Pasha et al, 2008;Roy et al, 2006).…”
Section: Dye Structure-associated Toxicitymentioning
confidence: 99%
“…For example, 2-methoxy-4-aminoazobenzene is an extremely weak mutagen, whereas 3-methoxy-4-aminoazobenzene is a strong hepatocarcinogen and mutagen (Esancy et al, 1990;Garg et al, 2002). Likewise, the presence of sulphonic groups on aromatic amines decreases their mutagenicity whereas the acetoxy Aromatic amines formed during anoxic conditions Dafale et al (2010) (COCH 3 ) substituent increases their mutagenic effects (Pasha et al, 2008;Roy et al, 2006).…”
Section: Dye Structure-associated Toxicitymentioning
confidence: 99%
“…We followed the same methodology previously proposed by our group (Pasha et al, 2008) for the calculation of CoMFA and CoMSIA descriptors.…”
Section: Calculation Of Comfa and Comsia Descriptorsmentioning
confidence: 99%
“…Particularly, the combination of various QSAR techniques such as Quantum QSAR, hologram quantitative structure-activity relationship (HQSAR), comparative molecular field analysis (CoM-FA), and comparative molecular similarity indices analysis (CoMSIA) (Pasha et al, , 2008(Pasha et al, , 2010Singh et al, 2004;Srivastava et al, 2005) has proven the quite successful role in the modern drug discovery. In order to facilitate the design of more specific and potent inhibitors, we must improve our understanding of the principles of molecular recognition for the PfPK7 enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…QSAR techniques increase the probability of success and reduce the time and cost involved in the drug discovery process (Blair et al, 1977;Greco, et al, 1992). Various methods, such as QSAR based on physical and electronic properties, are used in practice (Pasha et al, 2008(Pasha et al, , 2007a(Pasha et al, , 2005aSingh et al, 2004a). Previously a number of QSAR studies on classic BDZ molecules have been reported (Greco et al, 1992;Gupta, 1995;Gupta et al, 1996;HadjipavlouLitina et al, 2004).…”
Section: Introductionmentioning
confidence: 99%